Nutrient digestibility of vegetables waste flour on male quail (Coturnix coturnix japonica). (March 2018) - Pramono, A; Primadhani, M S; Swastike, W; Sutrisno, J
Abstract: The aim of this research is to determine the nutrient digestibility of vegetables waste flour on of male quail. Four hundred male quails were divided into four groups with five replications. The experiment is Completely Randomized Design and the data were analyzed by analyses of variants. The experimental diets were P0 = basal diet, P1 = 97% basal diet + 3% vegetables waste flour, P2 = 94% basal diet + 6% vegetables waste flour, and P3 = 91% basal diet + 9% vegetables waste flour. The observed variables were the digestibility of dry matter, crude protein and extract ether. Result showed that of the addition of vegetable waste flour in the diet had no effect on crude protein digestibility (P>0.05), however shown significant effect on dry matter (P <0.01) and extract ether (P <0.01) digestibility.